STABILITY-INDICATING REVERSED-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF METHYLCOBALAMIN, ALPHA-LIPOIC ACID, PYRIDOXINE HCL, AND FOLIC ACID IN BULK AND COMBINED DOSAGE FORM - V, Padmaja; M, Prasanthi; P, Mayuri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objectives: The purpose of the research is to develop a simple, precise, economical, accurate, reproducible, and sensitive method for the estimation of methylcobalamin, alpha-lipoic acid, pyridoxine hydrochloride, and folic acid drug product by reversed-phase high-performance liquid chromatography (RP-HPLC) method. Methods: New analytical method was developed for the estimation of methylcobalamin, alpha-lipoic acid, pyridoxine hydrochloride, and folic acid in drug product by RP-HPLC. The chromatographic separation was achieved on the Inertsil C18, 250 mm × 4.6 mm, 5 μm at ambient temperature. The separation achieved employing a mobile phase consists of buffer (added 5.05 g hexane-1-sulfonic acid is dissolved into 1000 mL of distilled water):acetonitrile in the ratio of 10:90% v/v. The flow rate was 1 mL/min and UV-visible spectrophotometer at 285 nm. The average retention time for methylcobalamin, alpha-lipoic acid, pyridoxine hydrochloride, and folic acid was found to be 3.5, 6.7, 8.5, and 9.3, respectively. Results: The developed method was validated as per ICH guidelines. All validation parameters were within the acceptable ranges. The assay methods were found to be linear from 0 to 2130 μg/mL for methylcobalamin, 0 to 142.5 μg/mL for alpha-lipoic acid, 0–4.54 μg/mL for pyridoxine hydrochloride, and 0–2 μg/mL for folic acid. The correlation coefficient was 0.999 for all drugs, respectively. The mean percentage values for the developed method were found to be within the range of 98–100.6%. The developed method was also found to be robust. Conclusion: It is concluded that developed method was accurate, precise, linear, reproducible, robust, and sensitive.